Government Political Intervention in Educational Implementation - Maulidah Hasnah Anas; Muhammad Sirozi; Solihah Titin Sumanti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research discusses the political intervention of the city government in the implementation of education in urban areas. Political intervention by city governments is often seen as an effort to improve the quality of education, but in practice, this intervention can give rise to various problems and challenges. This research uses qualitative methods with a case study approach in several cities in Indonesia to explore the impact and implications of political intervention on the education system. The research results show that political intervention can influence education policies, budget allocations, and decision-making processes in schools. Apart from that, this intervention also has an impact on the quality of education received by students and the professionalism of teaching staff. This research concludes that although the intention of political intervention is to improve the education system, its implementation needs to be carried out carefully, considering the possible long-term impacts.